Effect Of Cytokinin BA And Different Concentrations Of Chemical Stress Treatments On The Multiplication Of Vegetative Shoots Of The Plant Antirrhinum Magus L. Grown In Vitro - Mazene, Lamyaa Hussein Mousa; Mazeni, Shaymaa Hussein Mousa (South Eastern European Journal of Public Health, 2024)
The study was conducted on the multiplication of Antirrhinum magus L. plant using the micropropagation technique, represented by culture vegetative shoots on MS nutrient medium prepared with different concentrations of cytokinin BA and different levels of chemical stress treatments. The treatment of 4.44 μmol.L–1 BA with a NAA concentration of 0.54 μmol.L–1 gave the highest significant increase in the average number of vegetative shoots per plantlet, shoot length, number of leaves per plantlet, and leaf width, which amounted to 6.40 shoot explant-1, 4.00 cm, 20.60 shoot leaves -1, 0.68 cm, respectively, while a significant decrease in the average vegetative traits was observed when the concentration of BA in the medium was increased in the two treatments (8.88, 11.10) μmol.L–1 BA, which did not differ significantly between them. The results of chemical stress showed that reducing the level Mannitol to 15gm L-1 in multiplication medium led to a significant and inverse increase in the average number of vegetative shoots per plantlet, shoot length, number of leaves per shoot, and leaf width reached 4.80 shoot explant-1, 3.50 cm, 11.40 shoot explant1-, 0.44 cm in succession, and their averages decreased. By increasing the concentration in the middle. It was also observed that there was an inverse relationship between the average vegetative traits and the levels of PEG8000, where the control treatment achieved the highest significant increase in the average of all vegetative traits, amounting to 6.60 shoot explant-1, 4.06 cm, and 7.60 shoot explant-1, 0.92 cm, respectively, compared to the other averages of water stress whenever the level of PEG8000 increased. In the nutrient medium down to the level of 45g. L-1.